Two new taxa of leafy liverworts (Marchantiophyta: Jungermanniidae) from Cerro Plateado, Cordillera del Cóndor, Ecuador - Benitez Chavez, A. (2017)
Bazzania arcuata var. mamillosa var. nov. and Syzygiella ciliata sp. nov. are described from Cerro Plateado, the highest peak in the Cordillera del Cóndor, southern Ecuador. Bazzania arcuata var. mamillosa differs from the widespread neotropical B. arcuata by mamillose leaf cells and somewhat different dimensions of leaves and underleaves. Syzygiella ciliata (S. sect. Anomalae) differs from all other species described in the genus Syzygiella by having leaves with 2-3 very long ciliate teeth at the apex, with up to 10 cells long uniseriate tips, and 1-5 additional, shorter, ciliate teeth (to 5 cells long) on upper leaf margins. In other species of Syzygiella, teeth on vegetative leaves are lacking or shorter and fewer in number. Additional characters of the new Syzygiella species include the flattened stems with a pronounced, 2-3 cells wide cortex, rather large leaf cells and a densely papillose cuticle. © 2014 J. Cramer in Gebr. Borntraeger Verlagsbuchhandlung, Stuttgart, Germany.